In Vitro Activity of Essential Oils Distilled from Colombian Plants against Candidaauris and Other Candida Species with Different Antifungal Susceptibility Profiles (2022)
ABSTRACT: Multi-drug resistant species such as Candida auris are a global health threat. This scenario has highlighted the need to search for antifungal alternatives. Essential oils (EOs), or some of their major compounds, could be a source of new antifungal molecules. The aim of this study was to evaluate the in vitro activity of EOs and some terpenes against C. auris and other Candida spp. The eleven EOs evaluated were obtained by hydro-distillation from different Colombian plants and the terpenes were purchased. EO chemical compositions were obtained by gas chromatography/mass spectrometry (GC/MS). Antifungal activity was evaluated following the CLSI standard M27, 4th Edition. Cytotoxicity was tested on the HaCaT cell line and fungal growth kinetics were tested by time-kill assays. Candida spp. showed different susceptibility to antifungals and the activity of EOs and terpenes was strain-dependent. The Lippia origanoides (thymol + p-cymene) chemotype EO, thymol, carvacrol, and limonene were the most active, mainly against drug-resistant strains. The most active EOs and terpenes were also slightly cytotoxic on the HaCaT cells. The findings of this study suggest that some EOs and commercial terpenes can be a source for the development of new anti-Candida products and aid the identification of new antifungal targets or action mechanisms.